Sustainable living with environmental risks - Kaneko, Nobuhiro, 1959-; Yoshiura, Shinji; Kobayashi, Masanori (Tokyo : Springer, 2014)
We are not free from environmental risks that accompany the developm ent of human societies. Modern economic development has accelerated env ironmental pollution, caused loss of natural habitats, and modified lan dscapes. These environmental changes have impacted natural systems: wat er and heat circulation, nutrient cycling, and biodiversity. These chan ges in natural systems degrade ecosystem services and subsequently incr ease environmental risks for humans., Environmental risks, therefore, a re not only human health risks by pollution, climatic anomalies, and na tural disasters, but also degradation of ecosystem services on which mo st people are relying for their lives. We cannot entirely eliminate the risks, because it is not possible to attain zero impact on the environ ment, but we need to find a mechanism that minimizes environmental risk s for human sustainably. This is the idea of the interdisciplinary fram ework of "environmental risk management" theory, which advocates harmon y between economic development and environmental conservation. Based on this theory, the Sustainable Living with Environmental Risk (SLER) pro gramme, adopted by the Japanese Ministry of Education (MEXT) as one of its strategic programmes, has been training graduate students at the Yo kohama National University, Japan, from 2009 to 2013 to become future e nvironmental leaders who will take the initiative in reducing the level of environmental risks and in protecting natural resources in the deve loping nations of Asia and Africa. This book provides students and teac hers of this new academic field with a comprehensive coverage of case s tudies of environmental risks and their practical management technologi es not only in Japan but also in developing nations in Asia and Africa.
Managing Environmental Risks and Promoting Sustainability: Science A dvancement and Leadership Development -- Biodiversity Agriculture Suppo rts Human Populations -- Conservation and Sustainable Management of Soi l Biodiversity for Agricultural Productivity -- Conservation Tillage As sessment For Mitigating Greenhouse Gas Emission In Rainfed Agro-Ecosyst em -- Improving Biodiversity in Rice Paddy Fields to Promote Land Susta inability -- Agroforestry Models for Promoting Effective Risk Managemen t and Building Sustainable Communities -- Managing Environmental Risks and Promoting Sustainability: Conservation of Forest Resources in Madag ascar -- Community-Based Mangrove Forest Management in Thailand: Key Le sson Learned for Environmental Risk Management -- Necessity of Adaptive Risk Management for Fisheries and Wildlife -- Valuation of Non-Markete d Agricultural Ecosystem Services and Food Security in Southeast Asia - - Emerging Socio-Economic and Environmental Issues Affecting Food Secur ity: A Case Study of Silang-Santa Rosa Subwatershed -- Strengthening th e Capacity of Flood-Affected Rural Communities in Padang Terap, State o f Kedah, Malaysia -- Mitigating Coastal Erosion in Fort Dauphin, Madaga scar -- Risk Management of Chemical Pollution: Principles from the Japa nese Experience -- Research on the Sod Between Chlorophyll-a and Organi c Matter BOD, COD, Phosphorus and Total Nitrogen in Stagnant Lake Basin s -- Managing Construction Development Risks to the Environment -- Ecos ystem Restoration Using the Near-Natural Method in Shanghai -- Sustaina ble Management of Urban Green Environments: Challenges and Opportunitie s -- Environment and Social Capacity Assessment for Sustainability Prom otion and Risk Management -- Rural Landscape Conservation in Japan: Les sons from the Satoyama Conservation Program in Kanagawa Prefecture -- E nhancing Students' Ecological Thinking to Improve Understanding of Envi ronmental Risk -- Interactive Multimedia Education System (IMES) as a I nternational Education Platform.
Keywords: Sustainable living